Volyn-Polissian Dialect in Volodymyr Lys's Novel “Old Cholera”: Morphological Level (Linguostylistic Studies, 2020)
Incorporating dialect phenomena into modern literary text and the study of the individual author's technique of using them in literary work is one of the most topical issues of modern linguistics. It is an important source of information about the trends of dialect and literary language interaction.In this context, the writers' interest in North-Ukrainian dialects deserves special attention, in particular, the actualization of the Volyn-Polissian lingual elements in fiction. Volodymyr Lys shows unique mastery in reproducing the vivid dialect elements of Volyn Polissia in his works.The source of factual material for the case study is the novel Old Cholera by Volodymyr Lys. Although a considerable amount of research has been devoted to the writer's artistic language, few attempts have been made to investigate this novel, and it contains rich material for linguistic and dialectological studies.The purpose of the study is to trace the morphological features of the Volyn-Polissian dialect in Volodymyr Lys's novel Old Cholera.The study of the analyzed material has revealed that the writer conveyed, in the most detailed and consistent way, the dialectal differences in phonetic design, morpheme structure, and inflection of pronouns. Expressive dialectal phenomena illustrate the specifics of the formation of nouns and differences in the morpheme composition of adverbs. Several examples present local features of the phonetic framing and inflection of numerals. Differences in the system of adjective formation are evidenced by single dialectal phenomena. The examples with local verbs declension features are limited in number. Given the origin, morphological innovations dominate, the reasons for which are typical for the described area phonetic patterns, and similar processes.The individual author's feature of using the elements of dialect speech not only in the dialogues of characters but in the author narrative is considered as a successful artistic technique. It impresses with the effect of natural speech and is perceived as a subjective narrative-confession/
Keywords: Volyn-Polissian dialect,; inflection,; ending,; archaism,; grammatical analogy,; phonetic innovation.